(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
The magazine Pequenas Empresas, Grandes Negócios (PEGN), published by Globo, is a business media, which defines itself as “the largest and most important community of entrepreneurs in Brazil”. This work aims to investigate the conceptions of entrepreneurial youth present in texts published on the vehicle’s website, in 2018 and 2019. Through Discourse Analysis, we identified three major semantic axes, which structure the narratives. They show the youth as an entrepreneur who inspires society; as the one in which we should invest, so that the country can develop through its entrepreneurial actions; and the one who transforms youth into an enterprise. Such representations are presented most of the time as cases of success, or, when errors appear, they serve to the entrepreneurial pedagogy. The goal, in all of them, is to unify Brazilian youth by the entrepreneurial ethos.